Lifestyle and Financial Literacy: Determining Factors of Consumptive Behaviour Among Students Receiving KIP Scholarships in the Management Study Programme at UKI Toraja - Dwibin Kannapadang; Yohanis Lotong Ta’dung (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Consumptive behaviour is a tendency for individuals to purchase or consume goods and services excessively, without considering their actual needs, and often influenced by emotional, social, or trend factors. This study aims to analyse the influence of lifestyle and financial literacy on the consumptive behaviour of students receiving KIP scholarships in the management study programme at UKI Toraja. Sixty-five respondents were selected using proportional random sampling, consisting of four cohorts from 2021 to 2024. Hypothesis testing was conducted using Multiple Regression Analysis with the Statistical Package for the Social Sciences (SPSS) version 26 software tool. The results showed that, partially, lifestyle had a positive and significant effect on consumptive behaviour, while financial literacy had a negative and significant effect on consumptive behaviour. Simultaneously, lifestyle and financial literacy influenced consumptive behaviour. The coefficient of determination R-squared value of 0.524 indicates that the variable of consumptive behaviour of KIP scholarship recipients in the UKI Toraja management study programme is determined by lifestyle and financial literacy by 52.4%, while the remaining 47.6% is determined by factors other than the independent variables in this study.